The Urgent Need for Enhanced Surveillance and Research on Avian Influenza Possible Pandemic - Mehmood, Asim; Riaz, Areeba (Infectious Diseases Journal of Pakistan, 2024)
This letter underscores the critical need for intensified surveillance and research on avian influenza, particularly concerning strains with pandemic potential like H5 and H7 viruses. It discusses historical outbreaks and recent cases of highly pathogenic avian influenza infections in various animal species, including dairy cows, illustrating the evolving threat. The letter emphasizes the necessity of developing broad-spectrum vaccines to combat diverse avian influenza subtypes and understanding transmission dynamics between different animal species. It also advocates for a reassessment of human-wildlife interactions to prevent zoonotic disease emergence. Overall, this contribution adds to the ongoing dialogue on pandemic preparedness and One Health strategies, providing valuable insights into mitigating public health risks associated with avian influenza.